2015
DOI: 10.1007/s10461-015-1177-9
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Predicts Number of Sexual Partners for Female but not Male STI Clinic Patients

Abstract: This study tested the hypothesis that greater alcohol involvement will predict number of sexual partners to a greater extent for women than for men, and that the hypothesized sex-specific, alcohol—sexual partner associations will hold when controlling for alternative sex-linked explanations (i.e., depression and drug use). We recruited 508 patients (46% female, 67% African American) from a public STI clinic. Participants reported number of sexual partners, drinks per week, maximum drinks per day, frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
(63 reference statements)
3
13
1
Order By: Relevance
“…Among FSWs in Kenya, binge drinkers were more likely to report having unprotected sex and having a sexually transmitted infection (STI) than non-binge drinkers (Chersich et al, 2007). In addition, greater alcohol use has been associated with greater number of sex partners among female STI clinic patients (Carey et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Among FSWs in Kenya, binge drinkers were more likely to report having unprotected sex and having a sexually transmitted infection (STI) than non-binge drinkers (Chersich et al, 2007). In addition, greater alcohol use has been associated with greater number of sex partners among female STI clinic patients (Carey et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Both men who have sex with men (MSM) and women who have sex with women (WSW) have higher rates of substance use than their heterosexual counterparts (Cochran et al, 2004, McCabe et al, 2009) and the relationship between particular substances used and sexual risk varies across gender and partner gender (LaBrie et al, 2005; Leigh et al, 2008; Scott-Sheldon et al, 2009). A 2016 study found that heavy alcohol use is associated with multiple partners for women and men who have sex with men (MSM) only, but not for heterosexual men, demonstrating how partner gender may impact the extent to which specific drugs increase sexual risk behaviors (Carey et al, 2016). A literature review exclusive to MSM showed that binge drinking and methamphetamine use are consistently associated with risky sexual behaviors and concluded that not enough research had been conducted with other substance types (Vosburgh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the aforementioned challenges facing youth in the South, researchers have been compelled to identify variables that reliably predict RSBs within these populations. One variable frequently linked to RSBs is substance use (SU) (Carey, Senn, Walsh, Scott-Sheldon, & Carey, 2016; King, Nguyen, Kosterman, Bailey, & Hawkins, 2012; see Ritchwood, Ford, DeCoster, Sutton, & Lochman, 2015 for review; Tucker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the relation between SU and RSB is complex and has produced mixed findings; some studies have found strong relations between the two variables (e.g., Tucker et al, 2014) while others have shown more limited associations (e.g., Carey et al, 2016; Walsh, Fielder, Carey, & Carey, 2014). Contradictory findings are partially due to variations in the types of substances and RSBs examined, as well as differences in population-level characteristics (e.g., Leigh, Ames, & Stacy, 2008; Ritchwood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation